Computing the Distributions of Economic Models via Simulation - Stachurski, John; Martin, Vance (Econometrica, 2008)
We study a Monte Carlo algorithm for computing marginal and stationary densities of stochastic models with the Markov property, establishing global asymptotic normality and OP(n–1/2) convergence. Asymptotic normality is used to derive error bounds in terms of the distribution of the norm deviation.